1993
DOI: 10.1149/1.2056192
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ultrafine RuO2 ‐ TiO2 Binary Oxide Particles by a Sol‐Gel Process

Abstract: Ultrafine binary oxide particles of RuQ-TiO2 have been prepared by a sol-gel process consisting of hydrolysis and condensation of metal alkoxides in the liquid phase. This process enabled us to obtain desired rutile-type solid solution oxides of ruthenium and titanium with well-defined stoichiometry, except for the Ti-rich oxide composition, which appear not to form a homogeneous solid solution.) unless CC License in place (see abstract). ecsdl.org/site/terms_use address. Redistribution subject to ECS terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
2

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 0 publications
2
30
0
2
Order By: Relevance
“…consistent with the observations of Haas et al, 5 Kameyama et al, 49 and Colomer and Jurado 27 who did not see the formation of a uniform Ti 1-X Ru X O 2 solution at X ∼0.25 and below. This is contrary to the study of Wang 6 et al who claimed that they synthesized Ti 0.9 Ru 0.1 O 2 catalyst support.…”
Section: Resultssupporting
confidence: 91%
“…consistent with the observations of Haas et al, 5 Kameyama et al, 49 and Colomer and Jurado 27 who did not see the formation of a uniform Ti 1-X Ru X O 2 solution at X ∼0.25 and below. This is contrary to the study of Wang 6 et al who claimed that they synthesized Ti 0.9 Ru 0.1 O 2 catalyst support.…”
Section: Resultssupporting
confidence: 91%
“…[7], the authors referred to that the precursor containing Ru 3+ was oxidized not by oxygen but by disproportionation when the particle size was large. No Ru metallic phase was observed in the RuO 2 -TiO 2 binary oxides since the particle size was reduced by the Ti-additive effect [14] . However, in this work, the metallic Ru phase can not be explained only by the particle size or disproportionation.…”
Section: Xrd Patterns Analysismentioning
confidence: 96%
“…The citrate process in the synthesis of highly dispersed mixed oxides and solid solutions, has been used extensively [10][11][12] . Though the method is fairly simple, higher calcinations temperatures have been reported and requires an oxidizing agent and necessarily a fuel in the reaction mixture [13,14] . In the present work, the nanostructured RuO 2 -SnO 2 by the citrate-gel method was synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] In this regard, the sol-gel process may serve as a good approach to prepare oxide powders or films of this system and several studies have been found in the literature about it. [2][3][4][5][6][7][8][9] The advantage of using this technique is that one could find electrode structures which possess in principle a uniform and homogeneous distribution of electrocatalytically active ruthenium contacts throughout the electrode microstructure, which is not possible to obtain by the conventional decomposition methods. However, a serious drawback in the processing of materials based on RuO 2 is the well-established chemical reactivity above ∼700 • C where RuO 2 becomes volatile and oxidizes to RuO 3 a vacuum).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] The advantage of using this technique is that one could find electrode structures which possess in principle a uniform and homogeneous distribution of electrocatalytically active ruthenium contacts throughout the electrode microstructure, which is not possible to obtain by the conventional decomposition methods. However, a serious drawback in the processing of materials based on RuO 2 is the well-established chemical reactivity above ∼700 • C where RuO 2 becomes volatile and oxidizes to RuO 3 a vacuum). 11 The advantage of adding a second oxidic phase, such as ZrO 2 , TiO 2 , etc., is not only to reduce costs but also to provide a stabilization of the RuO 2 phase against oxidation or reduction processes.…”
Section: Introductionmentioning
confidence: 99%